Adsorption of sulfonated dyes by polyaniline emeraldine salt and its kinetics - Mahanta, Debajyoti; Madras, Giridhar; Radhakrishnan, S.; Patil, Satish (Journal of Physical Chemistry B, 2008)
A method for the removal of anionic (sulfonated) dyes from aqueous dye solutions using the chemical interaction of dye molecules with polyaniline is reported. Polyaniline (PANI) emeraldine salt was synthesized by chemical oxidation. Sulfonated dyes undergo chemical interactions with the charged backbone of PANI, leading to significant adsorption of the dyes. This phenomenon of selective adsorption of the dyes by PANI is reported for the first time and promises a green method for removal of sulfonated organics from wastewater. The experimental observations from UV-vis spectroscopy, X-ray diffraction, and conductivity measurements rule out the possibility of secondary doping of polyaniline salt by sulfonated dye molecules. A possible mechanism for the chemical interaction between the polymer and the sulfortated dye molecules is proposed. The kinetic parameters for the adsorption of sulfonated dyes on PANI are also reported.